1992
DOI: 10.1073/pnas.89.8.3463
|View full text |Cite
|
Sign up to set email alerts
|

Switching tRNA(Gln) identity from glutamine to tryptophan.

Abstract: The middle base (U35) of the anticodon of tRNAGII is a major element ensuring the accuracy of aminoacylation by Escherichia coUl glutaminyl-tRNA synthetase (GlnRS). An opal suppressor of tRNAGI, (su+2UGA) containing C35 (anticodon UCA) was isolated by genetic selection and mutagenesis. Suppression of a UGA mutation in the E. colifol gene followed by N-terminal sequence analysis of purified dihydrofolate reductase showed that this tRNA was an efficient suppressor that inserted predominantly tryptophan. Mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…Steady-state MichaelisMenten kinetics of GlnRS mutants showed that its specific aminoacylation of tRNA Gln was primarily reflected in lower mutant k cat values (25,26). Pre-steady state observations were made more recently for selectivity of GlnRS for glutamine versus glutamic acid (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Steady-state MichaelisMenten kinetics of GlnRS mutants showed that its specific aminoacylation of tRNA Gln was primarily reflected in lower mutant k cat values (25,26). Pre-steady state observations were made more recently for selectivity of GlnRS for glutamine versus glutamic acid (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that only Trp-inserting tRNA Trp suppressor tRNAs allowed induction raised the possibility that reading of codon 12 by tRNA Trp or insertion of Trp during translation of codon 12, or both, was necessary for induction. To distinguish between these possibilities, we examined the ability of an altered tRNA Gln opal suppressor tRNA that inserts tryptophan, described by Rogers et al (29), to allow tryptophan induction. The data in Table 5 indicate that replacing Trp codon 12 by TGA (strain PDG 1170) eliminates induction and appreciably reduces base-level expression of the operon, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…The top of the acceptor stem and the anticodon loop have been shown to interact with Gln-RS and are considered as important identity sites (14,16 (12). The first letter R or D depicts the RNA or DNA origin of the sequence; the second letter indicates the amino acid in the one-letter code; the three first numbers (166) come from the name of the organism (E.coli) and the last number is the number of a particular sequence among isoacceptors.)…”
Section: Resultsmentioning
confidence: 99%
“…Even unique nucleotides (e.g. 20A in tRNAArg, (7)) or nucleotide pairs (3G-70U in tRNAAla, (6,16,23)) are recognized by the corresponding synthetases not as they are, but together with their surroundings. In other words, an identity site can be considered to consist of a set of identity tiles.…”
Section: Discussionmentioning
confidence: 99%